The Effect of Parenting Alliances and Demographic Characteristics on Nutritional Status in Children with Avoidant Restrictive Food Intake Disorder in Malang Regency, Indonesia - Yoyok B. Prasetyo; Nursalam Nursalam; Rachmat Hargono; Ahsan Ahsan; Kumboyono Kumboyono (Jurnal Ilmiah Kesehatan)
Avoidant restrictive food intake disorder (ARFID) is an eating problem in children,